Tecnologias e técnicas apropriadas para o desenvolvimento sustentável: o caso da indústria cerâmica de Russas-Ce - Pessoa, José Manoel Albuquerque de Paula (2004)
The red tile industry of Ceará state is of enormous socio-economic importance in terms of income generation, employment opportunities and supply of products with prices which are accessible to the civil construction sector. This contributes towards improvement of quality of life in alI regions of the state. On the other hand, the aforementioned industrial sector generally causes a significant environmental impact upon extraction of raw materials (clays) without prior technical planning and as a result of making intensive use of wood- burning kilns of low energy-efficiency. This contributes significantly towards desertification, erosion, pollution, loss of biodiversity, devastation of mineral and forest reserves, as well as decharacterization of the landscape and reduction of arable soils. In view of the above, the aim was established of evaluating the current situation from a technological and environmental standpoint in the framework of the ceramic industry in the county of Russas, where there is a large concentration of enterprises in this sector. This aim was accomplished through application of questionnaires in companies and research at the entities responsible, in order to arrive at the most efficient way in which technology and techniques should be employed. It was concluded that the sustainability of the ceramic industry in Russas, in general, is compromised in social, economic and environmental terms. Nevertheless, with implementation of programs and projects geared towards utilization of the technology and techniques suggested, it is believed that the situation can be reverted.